Análise de usabilidade de sistemas de pedidos online: estudo de caso Facilivery - Pereira, Gabriel Barros (2023)
The present study analyzes the usability of ordering system interfaces. It also involves the evaluation of user experience, interface design, and Nielsen’s heuristics. The methodology used includes data collection through the comparison of interfaces from similar systems to identify strengths and weaknesses of the selected systems. The primary methodology employed in this project is that of Jesse James Garrett, which is developed with a focus on the user because user experience is of paramount importance for the success of a product or system. It is one of the most robust methodologies for interface design. Through the analysis of similar systems, it was possible to identify strengths and areas for improvement in the analyzed interfaces, especially in the case of the Facilivery system. It is used as a case study with the aim of proposing solutions to enhance the usability of the interface, along with the development of a high-fidelity prototype to improve the user experience with Facilivery. The work was validated through usability tests with users, and the feedback from these tests contributed to refining the proposed interface